Girls and Young Women Negotiate Wellbeing during COVID-19 in Quebec. Issue 3 (1st December 2020) - Thompson, Jennifer A.; Fraser, Sarah L.; Perez, Rocio Macabena; Paquette, Charlotte; Frohlich, Katherine L.
Abstract: In this article, we feature photographs and cellphilms produced by 13 girls and young women (aged 13 to 19) from urban, rural, and Indigenous areas of Quebec, Canada during the COVID-19 pandemic. Framed within girls' studies, we present girls' and young women's creations and co-analysis about wellbeing during a period of lockdown. We explore how girls and young women restructured their routines at home as well as negotiated motivation and the pressure to be productive. We note that girls had more time than usual for creative activities and self-discovery and that they engaged with the politics of the pandemic and advocated for collective forms of wellbeing. Importantly, girls reported that participating in this research improved their wellbeing during this lockdown.